Fifteen-minute consultation: Assessment, surveillance and management of hemihypertrophy. Issue 3 (26th August 2017) - Mark, Catherine; Hart, Caroline; McCarthy, Anthony; Thompson, Andrew
Abstract : This article aims to provide a structured and concise guide for the general paediatrician managing a child with hemihypertrophy. Hemihypertrophy is a relatively uncommon condition. The significance is that a proportion of those affected are at risk of developing malignancies in childhood. For these children regular surveillance is required. We have outlined how one might assess and investigate a child presenting with hemihypertrophy. We have also formulated a practicable surveillance strategy which is in line with the current Royal College of Paediatrics and Child Health (RCPCH) guideline 'Wilms' tumour surveillance in at-risk children'.